Fulminant hepatic failure in a patient with advanced extragonadal germ cell tumour. (29th September 2010) - Young, Alison; Madi, Ayman; Treanor, Darren; Millson, Charles; Selby, Peter; Chester, John
Abstract : Fulminant hepatic failure (FHF) in association with metastatic cancer, without evidence of liver metastases, has not been previously reported in the literature. This report concerns a case of FHF in a 36-year-old man with advanced germ cell tumour arising from an extragonadal (retroperitoneal) primary. Liver function and encephalopathy improved following chemotherapy, suggesting prompt diagnosis and treatment may have cured the patient. Following completion of chemotherapy, he developed spontaneous bacterial endocarditis, requiring aortic valve replacement, a rare complication of curative chemotherapy. At 44 months post completion of chemotherapy, he has regained his premorbid performance status and has returned to work.